М.ЮСУФ ШЫҒАРМАЛАРЫНДА ТАЛМЕҲ УСЫЛЫНЫҢ ҚОЛЛАНЫЛЫЎЫ - Прекеева, А.; Қутлымуратов, К. (ILIM hám JÁMIYET, 2022)
The article is devoted to the art of talme in the work of M. Yusuf. The names of famous historical figures, examples from the names of epics and legends are given and interpreted.